Distribution of Bus Trips Based on Origin and Destination of Terminal Passengers in Surabaya City for Travel Movement in East Java Region: Sebaran Perjalanan Bus Berdasarkan Asal Tujuan Penumpang Terminal di Kota Surabaya untuk Pergerakan Perjalanan di Wilayah Jawa Timur - Wibisono, R. Endro; Haratama, Kusuma Refa (Universitas Negeri Surabaya, 2025)
In land transportation, the terminal is part of the transportation service network as a node of a series of land transportation networks in each city. High travel rates by public vehicles such as buses that are not matched by good traffic arrangements will cause problems such as congestion. The study was conducted to determine the pattern of travel movements (Trip Distribution) of bus passengers in several regions in East Java in an Origin-Destination Matrix (MAT) using the Synthetic Method, namely the Unsconstrained Gravity Model. Alternative methods for calibrating parameters in the gravity model are α and β, which are parameters of the barrier function (accessibility) between zones . The approach used in this research is a quantitative descriptive approach using the Google Earth application media to measure the distance between one city and another. The results obtained Alpha (α) value of 5.82 and the best R Square of 0.0917 with y = 13.682x for MAT Power and Beta (β) value of 0.0098 and the best R Square value of 0.0635 with y = 1E - 10x. The distribution modeling formula for East Java zone bus passengers .